Conciencia turística y su contribución al desarrollo del turismo en la provincia de San Martín - Ishuiza Tapullima, Raimundo (2008)
The present Thessi, titled "Tourist Concience and its contribution to the Development of the Tourism in San Martin's County", it leaves the opinion that the population's positive behavior influences in the satisfaction of the visited. For such reason this word has a general objetivice of describe and explain the tourist conscience contributes in the development the tourism of San Martin's county, measuring the importance the tourism like economic activity in the San martinense inhabitants., also it has been elaborated an interview for tourists and questionnaire for Experts topics in Tourism, for then to be compared with the population's answer. San Martin's County, thanks it's a place privileged because if its geographical location and it possesses many tourist resources , it nor allows alone to attract investment, also the facilities it has permits the stay the tourists. The tourist conscience is a topic of vital importance that will be introduced in the population, because we are the ones that we will have a direct contact with the visitors, allowing propitiate the rescue of values, guiding the population toward the consolidation of their cultural identity, and it promotes feelings of solidarity and tolerance with the population of their environment, as well as with the inhabitants of other cultures. So it been identified that the positive behavior of people constitutes a significant contribution in the decision of tourists of visit us again or recommend others visit us.